2007
DOI: 10.1055/s-2008-1065358
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Single Nucleotide Polymorphisms in the Melanocortin-4 Receptor Promoter in Infantile Spasms

Abstract: The present study shows that genetic variants in the MC4R promoter are associated with the development of infantile spasms. The rs11872992 polymorphism influences ACTH treatment responses in patients with infantile spasms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Outside the United States, tetracosactide, a synthetic ACTH compound, is frequently used; however, there are no comparative studies of tetracosactide and natural ACTH. Among randomized controlled trials, the clinical spasm and hypsarrhythmic EEG response rate to natural or synthetic ACTH has ranged from 42–87% of patients (Hrachovy et al., 1983, 1994b; Baram et al., 1996; Vigevano & Cilio, 1997; Lux et al., 2004), and associations between genetic polymorphisms of the MC2R and MC4R genes and variability in ACTH responsiveness in IS are currently being examined (Liu et al., 2007, 2008b). The ongoing, NIH‐funded Epilepsy Phenome Genome Project is collecting 250 cases of cryptogenic IS as well as cases of IS with specific errors in brain development for detailed genetic analysis and will ultimately yield important information in this area.…”
Section: Therapeutic Options For Ismentioning
confidence: 99%
“…Outside the United States, tetracosactide, a synthetic ACTH compound, is frequently used; however, there are no comparative studies of tetracosactide and natural ACTH. Among randomized controlled trials, the clinical spasm and hypsarrhythmic EEG response rate to natural or synthetic ACTH has ranged from 42–87% of patients (Hrachovy et al., 1983, 1994b; Baram et al., 1996; Vigevano & Cilio, 1997; Lux et al., 2004), and associations between genetic polymorphisms of the MC2R and MC4R genes and variability in ACTH responsiveness in IS are currently being examined (Liu et al., 2007, 2008b). The ongoing, NIH‐funded Epilepsy Phenome Genome Project is collecting 250 cases of cryptogenic IS as well as cases of IS with specific errors in brain development for detailed genetic analysis and will ultimately yield important information in this area.…”
Section: Therapeutic Options For Ismentioning
confidence: 99%
“…Mc4r, leptin and Drd2 are present in the brain and hypothalamus, which are involved in regulating food intake and energy metabolism. Studies have demonstrated that the three genes can have antiepileptic effects in the brain (41)(42)(43). Therefore, the downregulated expression levels of Mc4r, Drd2 and leptin in the RS group in the present study may be associated with seizure propagation during epileptogenesis.…”
Section: Discussionmentioning
confidence: 50%
“…In addition, the following mechanisms are hypothesized to explain the effect of corticosteroids in the treatment of IS and LGS: immune regulation or inhibition, anti-inflammatory effect, increase of enzyme activity, regulating protein metabolism, regulating intracellular and extracellular electrolyte ratios, and regulating the intracellular glucose level [ 35 38 ]. In addition, the hypothalamic–pituitary–adrenal axis may also play an important role [ 39 ]. However, it is worth mentioning that the 35 individuals who responded to DEX treatment did not respond to an equivalent dose of prednisone in our study, suggesting that different corticosteroids have different therapeutic effect on IS and IS-related LGS and that there may be different mechanisms involved in the treatment of the diseases.…”
Section: Discussionmentioning
confidence: 99%